The Impact of Yoga on Mental Health - M. Kamraju (Universitas Pendidikan Indonesia (UPI), 2023)
Yoga has become increasingly popular as a form of exercise and relaxation in recent years, and its advantages for both physical and mental health are well known. This study examines yoga's impacts on mental health, including how it lowers stress and improves emotional stability. The study gives a general summary of yoga's theoretical and practical underpinnings, the medical research supporting its health advantages, and the difficulties and restrictions related to its application. The implications of these findings for the promotion of yoga as a complementary therapy are covered in the paper's conclusion.